2014
DOI: 10.1093/brain/awu162
|View full text |Cite
|
Sign up to set email alerts
|

Widespread grey matter pathology dominates the longitudinal cerebral MRI and clinical landscape of amyotrophic lateral sclerosis

Abstract: Menke/Koerner et al. use structural MRI to explore the extent of longitudinal changes in cerebral pathology in amyotrophic lateral sclerosis, and their relationship to clinical features. A characteristic white matter tract pathological signature is seen cross-sectionally, while cortical involvement dominates longitudinally. This has implications for the development of biomarkers for diagnosis versus therapeutic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
188
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 166 publications
(205 citation statements)
references
References 68 publications
16
188
0
1
Order By: Relevance
“…Rate of disability progression (ΔALSFRS‐R) was calculated as the decrease in ALSFRS‐R from a presumed baseline score of 48, divided by the disease duration in months from reported symptom onset. A measure of the burden of clinical UMN signs was based upon a pathological reflex sum score [Menke et al, 2014; Turner et al, 2004]…”
Section: Methodsmentioning
confidence: 99%
“…Rate of disability progression (ΔALSFRS‐R) was calculated as the decrease in ALSFRS‐R from a presumed baseline score of 48, divided by the disease duration in months from reported symptom onset. A measure of the burden of clinical UMN signs was based upon a pathological reflex sum score [Menke et al, 2014; Turner et al, 2004]…”
Section: Methodsmentioning
confidence: 99%
“…After initial assessment of 248 relevant documents with the search strategy, a total of 32 VBM studies on GM investigations in ALS patients versus healthy controls were identified, among which 9 did not report the whole brain stereotactic coordinates (Bede, et al, 2013,Cosottini, et al, 2012,Douaud, et al, 2011,Kassubek, et al, 2005,Lillo, et al, 2012,Menke, et al, 2014,Mioshi, et al, 2013,Tsujimoto, et al, 2011,Turner, et al, 2007 and 3 had overlapping data sets (Agosta, et al, 2014,Rajagopalan, et al, 2014,Tedeschi, et al, 2012. Finally, 22 case-control whole-brain data sets from 20 VBM studies (Agosta, et al, 2007,Canu, et al, 2011,Cerami, et al, 2014,Chang, et al, 2005,Cosottini, et al, 2013,Devine, et al, 2015,Ellis, et al, 2001,Grosskreutz, et al, 2006,Luo, et al, 2012,Meoded, et al, 2013,Mezzapesa, et al, 2007,Minnerop, et al, 2009,Rajagopalan and Pioro, 2014,Sage, et al, 2007,Senda, et al, 2011,Stoppel, et al, 2014,Tavazzi, et al, 2014,Thivard, et al, 2007,Trojsi, et al, 2014,Zhang, et al, 2014) that were composed of 454 ALS patients (mean age 56.5, 42.3% females) and 426 healthy controls (mean age 54.6, 48.3% females), met the inclusion criteria for the meta-analysis mentioned above ( Figure 1).…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
“…Contemporary research provides indications for a possible biological substrate of the suggested relationship between cognitive/behavioral decline and prognosis. For example, progressive grey matter abnormalities have been shown to be related to language deficits [38]. Moreover, recent research reports a possible link between specific genetic abnormalities, cognitive and behavioral impairment, and reduced survival [39] .…”
Section: Discussionmentioning
confidence: 99%